Martyres Pannoniae - the Chronological Position of the Pannonian Martyrs in the Course of Diocletian's Persecution - Jarak, Mirja (Array, 1996)
On the basis of the literary evidence, it is possible to establish a list of the Pannonian martyrs executed during the Diocletian's persecution. It is also possible to underline the place where the 4th edict was issued as well as the time of its publishing.